SELF INJURY IN ADOLESCENTS THAT MAY DISTURB THE MENTAL HEALTH - Ghaida Az-zahra Kusnadi (Psikoeduko: Jurnal Psikologi Edukasi dan Konseling, 2021)
The 2019 coronavirus disease (COVID-19) has greatly affected lives around the world. Isolation, contact restrictions, and economic shutdowns impose a complete change in the psychosocial environment in affected countries. Such actions have the potential to significantly threaten the mental health of children and adolescents. One of the impacts on mental health is doing self-injury. Self Injury is a form of behavior that is done by individuals to deal with pain emotionally by injuring themselves, done on purpose but not to commit suicide. Self Injury aims to change negative emotions into positive emotions in the perpetrator. The results showed that self-injury behavior, family background, and environment influence the formation of personality related to self-injury behavior, namely introvert personality, low self-esteem, rigid thought patterns, and difficulty communicating feelings. The form of self-injury that was carried out by the subject was cutting the wrists and pulling out large amounts of hair forcibly. Self-injury is carried out shortly after the perpetrator experiences an event that causes negative emotions and can occur as a result of a recalling process that causes negative emotions in a situation of solitude. Self-injury is an iceberg phenomenon that is common in the normal population and in patients who are clinically diagnosed as having mental disorders. This behavior has an increasing trend and can lead to suicide if not handled properly. Early detection and prevention of self-injury behavior are important to prevent premature death due to suicide.